If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -1) + 10(x + 2) = 4 Reorder the terms: 5(-1 + x) + 10(x + 2) = 4 (-1 * 5 + x * 5) + 10(x + 2) = 4 (-5 + 5x) + 10(x + 2) = 4 Reorder the terms: -5 + 5x + 10(2 + x) = 4 -5 + 5x + (2 * 10 + x * 10) = 4 -5 + 5x + (20 + 10x) = 4 Reorder the terms: -5 + 20 + 5x + 10x = 4 Combine like terms: -5 + 20 = 15 15 + 5x + 10x = 4 Combine like terms: 5x + 10x = 15x 15 + 15x = 4 Solving 15 + 15x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 15x = 4 + -15 Combine like terms: 15 + -15 = 0 0 + 15x = 4 + -15 15x = 4 + -15 Combine like terms: 4 + -15 = -11 15x = -11 Divide each side by '15'. x = -0.7333333333 Simplifying x = -0.7333333333
| 4x-5+x+7+4x+3=10x-8 | | 8x^2-25x-12=0 | | P^3+4p^2-21p=0 | | 3x^2-8x+4=768 | | 13x+12+234+342423+2=20 | | p=538.6225n-862700 | | (x+a)(x-b)=x^2-1 | | 3a+10=4(a-1) | | x-25=4x-61 | | 12-(2m+6)=3+3m-12 | | 11(5-y)+7=-7(y-4)-10 | | O=3t-2(4t-7) | | 4z+8-2z=6+z-1 | | 13-z=-6 | | x^3+3x^2-2x=O | | 6x-(5x-8)= | | 18y-11=14y-5 | | -4/3y-10=-1/6y+4 | | 7x-6=4(2x-2) | | 12x^2=-25x-12 | | 2x+(3x-1)-3=6 | | 3x^4+3x^3=12x^2+12x | | y=9x^3-25x^2-6x | | 9x-5=5(2x-4) | | 2x-(3x+10)=4x-35 | | 5(2x+2)=9x+2 | | 960=y*.12*2 | | 7[4-(5+4x)]-4x=-9+2(1-16x) | | 5x-40-3x=4x-4-2 | | -4y+4y+-9=15+-4y | | 0=4x^2-400x+23000 | | 2x+7-3x=4x-2 |